Starring Hitler! Adolf Hitler as the Main Character in Twentieth-First Century French Fiction - Marion Duval (Studies in 20th & 21st Century Literature, 2019)
Adolf Hitler has remained a prominent figure in popular culture, often portrayed as either the personification of evil or as an object of comedic ridicule. Although Hitler has never belonged solely to history books, testimonials, or documentaries, he has recently received a great deal of attention in French literary fiction. This article reviews three recent French novels by established authors: La part de l’autre (The Alternate Hypothesis) by Emmanuel Schmitt, Lui (Him) by Patrick Besson and La jeunesse mélancolique et très désabusée d’Adolf Hitler (Adolf Hitler’s Depressed and Very Disillusioned Youth) by Michel Folco; all of which belong to the Twenty-First Century French literary trend of focusing on Second World War perpetrators instead of their victims. It analyzes their portrayals of the Führer, noting how Hitler has been re-imagined as sexually deviant, comical and repulsive. It argues that these representations aim to understand the Führer but end up simultaneously reinforcing and obscuring his monstrosity through grotesque depictions of sexual deviance. In such a way, this overindulgence of various psychological explanations, gratuitous sex and dark humor make it significantly harder to grasp the reality of Hitler, almost to the point where it becomes impossible to understand his place in both history and the modern world.
Keywords: French; Fiction; Second World War Memory; Hitler; Nazi; Holocaust; Sexuality; Grotesque; Patrick Besson; Michel Folco; Eric-Emmanuel Schmitt